Patterns of cigarette, hookah and other tobacco product consumption habits among undergraduate students of the University of Sarajevo before the COVID-19 outbreak in Bosnia and Hercegovina, a cross-sectional study - Šljivo, A.; Ćetković, A.; Hašimbegović-Spahić, D.; Mlačo, N.; Mujičić, E.; Selimović, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Tobacco products represent a major health risk factor and a potent way to help transmission of COVID-19. Current data regarding consumption of these products in the region are scarce. The aim of this study was to evaluate patterns of cigarette, hookah and other tobacco products consumption among undergraduate students from the University of Sarajevo before the COVID-19 outbreak in the country.Methods. This cross-sectional study based on a National Youth Tobacco Survey (NYTS) was conducted among undergraduate students from the University of Sarajevo in Bosnia and Hercegovina via an online questionnaire from 22nd to 26th of January 2020. Results. Out of 605 students involved in the study, most of them were female (N=429, 70.9%); 363 (60.0%) were enrolled in medical sciences; 159 (26.3%) were attending the 3rd year of their curriculum; 224 (37%) were original from Canton Sarajevo and 514 (84.9%) were living in urban environment. Two hundred thirty five students out of 605 (38.8%) were current smokers and 117 (19.3%) hookah smokers. Being female (OR=0.539, 95% CI 0.368-0.790, p=0.002), in the 1st or 2nd year of study (OR=0.805, 95% CI 0.667-0.972, p=0.024) and living in a rural environment (OR=0.335, 95% CI 0.191-0.585, p